Ultrasonographic Assessment of Diaphragm Function in Critically Ill Subjects - Umbrello, Michele; Formenti, Paolo (Respiratory care, 2016)
The majority of patients admitted to the ICU require mechanical ventilation as a part of their process of care. However, mechanical ventilation itself or the underlying disease can lead to dysfunction of the diaphragm, a condition that may contribute to the failure of weaning from mechanical ventilation. However, extended time on the ventilator increases health-care costs and greatly increases patient morbidity and mortality. Nevertheless, symptoms and signs of muscle disease in a bedridden (or bed rest-only) ICU patient are often difficult to assess because of concomitant confounding factors. Conventional assessment of diaphragm function lacks specific, noninvasive, time-saving, and easily performed bedside tools or requires patient cooperation. Recently, the use of ultrasound has raised great interest as a simple, noninvasive method of quantification of diaphragm contractile activity. In this review, we discuss the physiology and the relevant pathophysiology of diaphragm function, and we summarize the recent findings concerning the evaluation of its (dys)function in critically ill patients, with a special focus on the role of ultrasounds. We describe how to assess diaphragm excursion and diaphragm thickening during breathing and the meaning of these measurements under spontaneous or mechanical ventilation as well as the reference values in health and disease. The spread of ultrasonographic assessment of diaphragm function may possibly result in timely identification of patients with diaphragm dysfunction and to a potential improvement in the assessment of recovery from diaphragm weakness.